A gravitational theory of reputation. For an interdisciplinary approach - Casini, Joe (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
This article aims to explore how the laws of gravitational physics can provide useful metaphors for understanding the nature of reputation in social and professional networks. We will analyse the key analogies between gravitation and reputation, concluding with a reflection on black holes and dark matter.